ChemInform Abstract: Phosphine Organocatalysis in the Synthesis of Natural Products and Bioactive Compounds. Issue 30 (4th July 2013) - Gomez, Catherine; Betzer, Jean‐Francois; Voituriez, Arnaud; Martinetti, Angela
Abstract Review: 47 refs.